1995
DOI: 10.1111/j.1432-1033.1995.806zz.x
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Acyltransferase Involved in Triacylglycerol Biosynthesis Complements an Escherichia Coli sn‐1‐acylglycerol‐3‐phosphate Acyltransferase Mutant

Abstract: The second acylation reaction in glycerolipid biosynthesis is catalyzed by an sn-1 -acylglycerol-3-phosphate acyltransferase. The enzyme of Lirnnunfhes douglusii involved in triacylglycerol synthesis has an unusual specificity for very long chain acyl groups in both of its substrates, namely acyl-CoA and S I I -1 -acylglycerol-3-phosphate, and causes the enrichment of erucoyl groups in the sn-2 position of the seed oil of this plant species. We have isolated a cDNA clone encoding this embryo-specific, microsom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Species in which the seed oils have uncommon acyl moieties at the sn-2 position possess additional seed-specific LPATs that are reactive toward the respective uncommon acyl-CoAs (Cao et al, 1990;Laurant and Huang, 1992;Brown et al, 1995;Frentzen, 1998). Genes encoding cytoplasmic LPATs in maturing seeds or other organs from several species, including maize (Zea mays) (Brown et al, 1994), coconut (Cocos nucifera) (Knutzon et al, 1995), and meadowfoam (Limnanthes alba) (Hanke et al, 1995) have been reported. The deduced amino acid sequences of the enzymes contain transmembrane segments indicative of association with membranes, and the enzyme from the leaf or seed extracts can be recovered in the microsomal fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Species in which the seed oils have uncommon acyl moieties at the sn-2 position possess additional seed-specific LPATs that are reactive toward the respective uncommon acyl-CoAs (Cao et al, 1990;Laurant and Huang, 1992;Brown et al, 1995;Frentzen, 1998). Genes encoding cytoplasmic LPATs in maturing seeds or other organs from several species, including maize (Zea mays) (Brown et al, 1994), coconut (Cocos nucifera) (Knutzon et al, 1995), and meadowfoam (Limnanthes alba) (Hanke et al, 1995) have been reported. The deduced amino acid sequences of the enzymes contain transmembrane segments indicative of association with membranes, and the enzyme from the leaf or seed extracts can be recovered in the microsomal fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The Ld-LPAAT gene was cloned and expressed under control of a seed specific promoter in rapeseed. However, this achievement was not accompanied by an increase in erucic acid content in the seed oil (Brown et al 1995;Hanke et al 1995;Lassner et al 1995;Brough et al 1996). In a second approach, the fae1 gene has been cloned from Arabidopsis (James et al 1995) and subsequently from rapeseed.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, storage triacylglycerols are synthesized via a four-step pathway that involves acylation of glycerol 3-phosphate at the sn-1 position to form LPA, acylation of LPA by LPAAT, and then conversion of the PA to diacylglycerol by PA phosphatase followed by sn-3 acylation to form triacylglycerol (21). Interest in this metabolic pathway from the perspective of understanding and manipulating plant oil production has resulted in the cloning of several plant cDNAs that encode enzymes with LPAAT activity (22)(23)(24)(25). Interestingly, these cDNAs have extensive * The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%